2015
DOI: 10.1515/pjvs-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Transport induced inflammatory responses in horses

Abstract: Deleterious response to road transport is an important problem in equine practice. It determines different physiological, immunological and metabolic changes which lead to increased susceptibility to several disorders such as pneumonia, diarrhea, colics, laminitis, injuries and rhabdomyolisis. The aim of our study was to look for possible relationships between transportation of female young and older horses over a long and short distance and an inflammatory state reflected by an increase of acute phase protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…No association was found on the whole population or on those horses that were surgically treated. This was unexpected because transport was considered as a stressful event, especially for critically ill patients [ 18 , 19 , 20 , 21 ]. Moreover, the time required to reach the clinic may affect the survival rate, because it increases the time from appearance of clinical signs to intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No association was found on the whole population or on those horses that were surgically treated. This was unexpected because transport was considered as a stressful event, especially for critically ill patients [ 18 , 19 , 20 , 21 ]. Moreover, the time required to reach the clinic may affect the survival rate, because it increases the time from appearance of clinical signs to intervention.…”
Section: Discussionmentioning
confidence: 99%
“…During transportation, dehydration may worsen due to stress, sweating, and absence of adequate fluid therapy. Transportation is also one of the main causes of stress for horses, as it is responsible of disruption of homeostasis [ 18 , 19 , 20 , 21 ]. Therefore, distance from and time required to reach the referral practice may worsen the clinical conditions of the horse and act as a predisposing factor.…”
Section: Introductionmentioning
confidence: 99%
“…Wessely‐Szponder et al. (2015) quantified MAD at slaughter in horses transported for 1 and for 12 h (in conditions pertaining to current EU legislation). The study involved fillies and older mares, but no information is given on the prejourney conditions, thereby limiting the interpretation of the results.…”
Section: Assessmentmentioning
confidence: 99%
“…Pearson correlation (expressed as value of r) between the dependant variables which reported at least one significant correlation The reported changes in the oxidative/antioxidative parameters, PTAS and ROMs, should also be interpreted as components of the acute phase response inducted by transport stress (Onmaz et al, 2011;Wessely-Szponder et al, 2015). We did not find a significant increase in ROMs, as reported in transported ewes (Piccione et al, 2013), however, peaks in oxidative products may be observed one or two days after transportation (Nazifi et al, 2009;Piccione et al, 2013;Wessely-Szponder et al, 2015), suggesting serial sampling during recovery might be considered in future studies. The highest ROMs values were observed on day 1 in EG horses in the current study, with a simultaneous and marked increase of PTAS, which was almost double the normal range (Kusano et al, 2016).…”
Section: Tablementioning
confidence: 99%